2008
DOI: 10.1519/jsc.0b013e318166052b
|View full text |Cite
|
Sign up to set email alerts
|

Does Performance of Hang Power Clean Differentiate Performance of Jumping, Sprinting, and Changing of Direction?

Abstract: The primary purpose of this study was to investigate whether the athlete who has high performance in hang power clean, a common weightlifting exercise, has high performances in sprinting, jumping, and changing of direction (COD). As the secondary purpose, relationships between hang power clean performance, maximum strength, power and performance of jumping, sprinting, and COD also were investigated. Twenty-nine semiprofessional Australian Rules football players (age, height, and body mass [mean +/- SD]: 21.3 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
115
0
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(148 citation statements)
references
References 35 publications
20
115
0
13
Order By: Relevance
“…The findings of this study are similar to those reported by Bosco et al 8 , and Hori et al 9 who found strong and moderate inverse relationships of r = -0.93 (p<0.01) between 30 m and CMJ and r = -0.69 (p<0.01) between 20 m and CMJ performances, respectively. The correlations in this study are not as strong as those reported by Bosco et al 8 although the subjects used in the earlier study were a mixed group of male and female jump athletes which may have increased the range of values attained.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The findings of this study are similar to those reported by Bosco et al 8 , and Hori et al 9 who found strong and moderate inverse relationships of r = -0.93 (p<0.01) between 30 m and CMJ and r = -0.69 (p<0.01) between 20 m and CMJ performances, respectively. The correlations in this study are not as strong as those reported by Bosco et al 8 although the subjects used in the earlier study were a mixed group of male and female jump athletes which may have increased the range of values attained.…”
Section: Discussionsupporting
confidence: 92%
“…2 To the author's knowledge, no previous research has been conducted in cricketers to allow for a comparison of sprint times tested over the same distances presented here, but the 20 m sprint times attained by the subjects in the present study (3.05 ± 0.11 s) were similar to those reported for semiprofessional Australian Rules football players 9 , as mentioned earlier, and to those of young well-trained footballers. 6,10 However, the international football players in the study by Wisloff et al 5 displayed much greater CMJ height (56.4 ± 4.0 cm), despite similar 20m sprint times (3.00 ± 0.30 s).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations